What Causes the Child Penalty? Evidence from Adopting and Same-Sex Couples - Andresen, Martin Eckhoff; Nix, Emily (Journal of Labor Economics, 2022)
New parenthood causes large decreases in labor market incomes for mothers but not fathers, a stylized fact known as the “child penalty.” We combine a simple household model with estimates of child penalties in heterosexual nonadopting, adopting, and same-sex couples to better understand what causes the child penalty in heterosexual nonadopting couples. Our results largely rule out giving birth and the father’s advantage in the labor market as mechanisms, leaving preferences, gender norms, and discrimination as the main explanations. In addition, our paper provides novel evidence on the impact of children on labor market outcomes of adopting and same-sex couples.